Constraints for implementing environmental remediation in Brazil: political and regulatory aspects related to uranium mines (Research, Society and Development, 2021)
Environmental remediation and decommissioning are trending topics to tecnological development, deserving particular attention. This paper consisted in identify constraints that may delay the decommissioning and environmental remediation of uranium mining and milling facilities, identifying possible sollutions. To do so, a search on specific websites and bibliographies was conducted, with the guidance of section 3 of the CIDER Project. Analysing the information gathered, Brazil does not have an adequate legal basis to guide the environmental remediation of uranium milling and mining facilities. Furthermore, it’s necessary that Brazil establishes a specific national policy, that promotes it’s objectives clearly and transparently throughout all the life cycle of environmental remediation projects.